No firm Is an Island? How industry conditions shape firms' expectations - Philippe Andrade; Olivier Coibion; Erwan Gautier; Yuriy Gorodnichenko (Federal Reserve Bank of Boston, 2020)
We study how firms' expectations and actions are affected by both aggregate and industryspecific conditions using a survey of French manufacturing firms. We document an important new stylized fact. In response to industry-level shocks that have no aggregate effects, firms' aggregate expectations respond persistently. This is consistent with "island" models in which firms use the local prices they observe to make inferences about broader aggregate conditions. We then assess the extent to which these patterns are related to observable characteristics of firms and the industries in which they reside. Finally, we extend the analysis to firms' expectations of their own future price changes and document how these respond to both industry and aggregate variation.
Keywords: E2; E3; E4; 330; expectations; rational inattention